Diabetes Is the Strongest Predictor of Limited Exercise Capacity in Chronic Heart Failure and Preserved Ejection Fraction (HFpEF) - Berisha-Muharremi, Venera; Henein, Michael Y.; Dini, Frank L.; Haliti, Edmond; Bytyçi, Ibadete; Ibrahimi, Pranvera; Poniku, Afrim; Batalli, Arlind; Tafarshiku, Rina; Elezi, Shpend; Bajraktari, Gani (Frontiers in Cardiovascular Medicine, 2022)
Background and Aim Type 2 diabetes mellitus (T2DM) is a known risk factor in patients with heart failure (HF), but its impact on phenotypic presentations remains unclear. This study aimed to prospectively examine the relationship between T2DM and functional exercise capacity, assessed by the 6-min walk test (6-MWT) in chronic HF. Methods We studied 344 chronic patients with HF (mean age 61 ± 10 years, 54% female) in whom clinical, biochemical, and anthropometric data were available and all patients underwent an echo-Doppler study and a 6-MWT on the same day. The 6-MWT distance divided the cohort into; Group I: those who managed ≤ 300 m and Group II: those who managed >300 m. Additionally, left ventricular (LV) ejection fraction (EF), estimated using the modified Simpson's method, classified patients into HF with preserved EF (HFpEF) and HF with reduced EF (HFrEF). Results The results showed that 111/344 (32%) patients had T2DM, who had a higher prevalence of arterial hypertension (p = 0.004), higher waist/hips ratio (p = 0.041), higher creatinine (p = 0.008) and urea (p = 0.003), lower hemoglobin (p = 0.001), and they achieved shorter 6-MWT distance (p < 0.001) compared with those with no T2DM. Patients with limited exercise (<300 m) had higher prevalence of T2DM (p < 0.001), arterial hypertension (p = 0.004), and atrial fibrillation (p = 0.001), higher waist/hips ratio (p = 0.041), higher glucose level (p < 0.001), lower hemoglobin (p < 0.001), larger left atrium (LA) (p = 0.002), lower lateral mitral annular plane systolic excursion (MAPSE) (p = 0.032), septal MAPSE (p < 0.001), and tricuspid annular plane systolic excursion (TAPSE) (p < 0.001), compared with those performing >300 m. In the cohort as a whole, multivariate analysis, T2DM (p < 0.001), low hemoglobin (p = 0.008), atrial fibrillation (p = 0.014), and reduced septal MAPSE (p = 0.021) independently predicted the limited 6-MWT distance. In patients with HFpEF, diabetes [6.083 (2.613–14.160), p < 0.001], atrial fibrillation [6.092 (1.769–20.979), p = 0.002], and septal MAPSE [0.063 (0.027–0.184), p = 0.002], independently predicted the reduced 6-MWT, whereas hemoglobin [0.786 (0.624–0.998), p = 0.049] and TAPSE [0.462 (0.214–0.988), p = 0.041] predicted it in patients with HFrEF. Conclusion Predictors of exercise intolerance in patients with chronic HF differ according to LV systolic function, demonstrated as EF. T2DM seems the most powerful predictor of limited exercise capacity in patients with HFpEF.